Pride and Prejudice: a critical view on nineteenth century English society - Regueral, Florencia (2006)
It has been remarked that though Jane Austen (1775-1817) lived through some of the greatest revolutionary movements of her time, like the French Revolution, the Industrial Revolution and the Napoleonic Wars, her novels conspicuously miss them out. Her experience of life was seemingly confined to a small circle of society, and that is what she was content to deal with. She wrote only what she knew of: the small society which surrounded her. Thus her novels are supposedly concerned with no other class than the clergy and the landed gentry, their customs and manners and Pride and Prejudice is no exception. Throughout the action of the novel Jane Austen looks at the nineteenth century traditional society with a critical eye. Thus the present paper intends to prove that it is through the characters' language, behaviour, comments and actions in Pride and Prejudice, especially those of the protagonist -Elizabeth- that the reader learns about the author's rejection of certain social conventions of the time.